Sulfide solid electrolyte and method for producing same
By using sulfide solid electrolytes containing sulfide glass phase in lithium-ion secondary batteries, the safety hazards of existing liquid electrolytes and the problems of insufficient battery performance are solved, and high lithium ion conductivity and battery characteristics are improved.
Patent Information
- Application Number
- CN202380053707.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-19
- Filing Date
- 2023-07-12
- Publication Date
- 2025-02-28
AI Technical Summary
The liquid electrolytes used in existing lithium-ion secondary batteries have safety hazards such as liquid leakage and fire, and the battery life is short and the operating temperature range is narrow. Solid electrolytes have challenges in improving safety and lithium ion conductivity.
A sulfide solid electrolyte containing a sulfide glass phase is used, and its composition mainly contains PS4 units relative to the P2S7 unit, and is manufactured by melting the raw material and subjecting to rapid cooling.
High lithium ion conductivity is achieved, the battery characteristics of lithium ion secondary batteries are improved, the contactability and uniformity of the electrolyte are enhanced, and the volume and cost of the battery are reduced.
Smart Images

Figure CN119546561A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a sulfide solid electrolyte and a method for producing the same. Background Art
[0002] Lithium-ion secondary batteries are widely used in portable electronic devices such as mobile phones and laptop computers.
[0003] In the past, liquid electrolytes have been used in lithium-ion secondary batteries, but there are concerns about leakage and fire, and the housing needs to be enlarged for safety design. In addition, improvements are also expected in terms of short battery life and narrow operating temperature range.
[0004] In view of this, all-solid-state lithium ion secondary batteries using a solid electrolyte as the electrolyte of the lithium ion secondary battery are attracting attention from the perspectives of improved safety, high-speed charging and discharging, and miniaturization of the housing.
[0005] Solid electrolytes are roughly divided into sulfide solid electrolytes and oxide solid electrolytes. The sulfide ions that constitute the sulfide solid electrolyte have a larger polarizability than the oxide ions that constitute the oxide solid electrolyte, and exhibit high lithium ion conductivity. As sulfide solid electrolytes, Li 10 GeP2S 12 LGPS type crystals, Li6PS5Cl and other argyrodite type crystals, Li7P3S 11 Glass-ceramics, LPS glass-ceramics, etc.
[0006] The Li-P-S system composition has a high potential window and low reactivity with active materials, and therefore has attracted attention as a sulfide solid electrolyte with excellent electrochemical stability.
[0007] For example, Patent Document 1 discloses a method for 31 A Li-P-S solid electrolyte having a ratio of 60 mol% to 100 mol% of crystals having a peak in the PNMR spectrum. 31 A Li-P-S-Ha solid electrolyte in which the ratio of crystals having a unique peak in the PNMR spectrum is 60 mol % to 100 mol %, wherein Ha refers to a halogen element.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: International Publication No. 2007 / 066539
[0011] Patent Document 2: Japanese Patent Application Publication No. 2014-093262 Summary of the invention
[0012] However, for solid electrolytes that precipitate crystals at a high volume fraction, the contact between the electrolytes and the contact between the electrolyte and the active material is poor. In addition, since the heat treatment conditions for crystallization are strict and the state varies due to slight differences in treatment, the quality of the solid electrolyte varies greatly.
[0013] In contrast, for a solid electrolyte comprising a glass phase, the contact between the electrolytes and the contact between the electrolyte and the active material is good. In addition, even when a solid electrolyte comprising a glass phase is crushed and used in a powdered form, the reduction in conductivity caused by the crushing is also very small. In addition, by melting the raw materials to make a solid electrolyte comprising a glass phase, the uniformity of the composition is also good and can be formed into any shape.
[0014] On the other hand, conventionally known Li—P—S-based sulfide glass has low lithium ion conductivity.
[0015] Therefore, an object of the present invention is to provide a sulfide solid electrolyte including a sulfide glass phase having high lithium ion conductivity and a method for producing the same.
[0016] The present inventors have conducted intensive studies and have found that the above-mentioned problems can be solved by a sulfide solid electrolyte containing a sulfide glass phase, which contains Ha in addition to Li, P, and S, and mainly contains PS4 units relative to P2S7 units, thereby completing the present invention. In addition, as a method for obtaining a sulfide solid electrolyte with high and uniform lithium ion conductivity, a manufacturing method of melting a raw material and rapidly cooling it has been found.
[0017] That is, the present invention relates to the following [1] to
[12] .
[0018] [1] A sulfide solid electrolyte comprising a sulfide glass phase, comprising a PS4 unit and a P2S7 unit, wherein the peak intensity of the PS4 unit in the Raman spectrum is (PS4) The peak intensity of the P2S7 unit I (P2S7) The ratio satisfies 0.05<{I (P2S7) / I (PS4)}<1.00, and the constituent elements include Li, P, S and Ha, wherein Ha is a halogen element, and the contents of the constituent elements are expressed in at% as Li: 30-50%, P: 5-15% and S: 30-60%.
[0019] [2] A sulfide solid electrolyte according to [1] above, wherein the Ha comprises at least one selected from the group consisting of F, Cl, Br and I, and the contents of the above constituent elements are expressed in at% as Li: 30-50%, P: 5-12%, S: 30-50% and Ha: 2-10%.
[0020] [3] The sulfide solid electrolyte according to [1] or [2], further comprising a P2S6 unit, wherein the peak intensity I of the P2S6 unit in the Raman spectrum is (P2S6) The peak intensity I of the P2S7 unit is (P2S7) The ratio satisfies 0.5<{I (P2S7) / I (P2S6) The relationship between}<10.
[0021] [4] The sulfide solid electrolyte according to [1] or [2] above, wherein the content ratio of Li to P in the above constituent elements expressed in at % satisfies the relationship of 2.5≤(Li / P)≤7.
[0022] [5] The sulfide solid electrolyte according to [1] or [2], wherein in the Raman spectrum, at a wave number of 150 to 180 cm -1 The region has a peak, and the full width at half maximum of the peak is 20 cm -1 above.
[0023] [6] The sulfide solid electrolyte according to [1] or [2] above, wherein the content of the sulfide glass phase is 50% by weight or more.
[0024] [7] The sulfide solid electrolyte according to [1] or [2] above, which is used for a lithium ion secondary battery.
[0025] [8] A method for producing a sulfide solid electrolyte, comprising the following steps: mixing raw materials containing lithium, sulfur and phosphorus to obtain a raw material mixture, heating and melting the raw material mixture in a gas atmosphere containing sulfur to obtain a molten material, and rapidly cooling the molten material to obtain a solid; the ratio of the content of the lithium element to the phosphorus element in the raw material mixture expressed in at% is Li / P ≥ 2.5, and the cooling rate of the rapid cooling is 500°C / second or more.
[0026] [9] The method for producing a sulfide solid electrolyte according to [8] above, wherein a raw material containing a halogen element is further mixed to obtain the raw material mixture.
[0027]
[10] The method for producing a sulfide solid electrolyte according to [8] or [9] above, wherein the heating temperature for the heating and melting is 600 to 950°C.
[0028]
[11] The method for producing a sulfide solid electrolyte according to [8] or [9] above, wherein the contents of the elements when the raw materials are mixed are expressed in at% as Li: 30 to 50%, P: 5 to 15%, and S: 30 to 60%.
[0029]
[12] A method for producing a sulfide solid electrolyte according to [8] or [9] above, wherein the contents of the elements when mixing the above raw materials are expressed in at% as Li: 30-50%, P: 5-12%, S: 30-50% and Ha: 2-10%.
[0030] The sulfide solid electrolyte according to the present invention can achieve high lithium ion conductivity even when containing a sulfide glass phase, and is therefore very useful as a solid electrolyte for lithium ion secondary batteries, and can be expected to improve the battery characteristics of lithium ion secondary batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 : is a flowchart showing the method for producing the sulfide solid electrolyte according to the present embodiment.
[0032] Figure 2 : is a flowchart showing the method for producing the sulfide solid electrolyte according to the present embodiment.
[0033] Figure 3 : is a flowchart showing the method for producing the sulfide solid electrolyte according to the present embodiment.
[0034] Figure 4 This is the Raman spectrum of the sulfide solid electrolyte of Example 1.
[0035] Figure 5 1 is the Raman spectrum of the sulfide solid electrolyte of Example 1 and the corrected spectrum after baseline correction.
[0036] Figure 6 This is a calculated spectrum obtained by adding a correction spectrum after baseline correction for the Raman spectrum of the sulfide solid electrolyte of Example 1, three spectra separated from the correction spectrum peak, and the three spectra.
[0037] Figure 7 This is a calculated spectrum obtained by adding a correction spectrum after baseline correction for the Raman spectrum of the sulfide solid electrolyte of Example 2, three spectra separated from the correction spectrum peak, and the three spectra.
[0038] Figure 8 This is a calculated spectrum obtained by adding a correction spectrum after baseline correction for the Raman spectrum of the sulfide solid electrolyte of Example 3, three spectra separated from the correction spectrum peak, and the three spectra. DETAILED DESCRIPTION
[0039] Hereinafter, the present invention will be described in detail, but the present invention is not limited to the following embodiments and can be arbitrarily deformed and implemented without departing from the gist of the present invention. In addition, "to" indicating a numerical range is used to include the numerical values recorded before and after it as the lower limit and upper limit. In addition, at% in this specification refers to atomic%, i.e., atomic%.
[0040] <Sulfide solid electrolyte>
[0041] The sulfide solid electrolyte (hereinafter, sometimes simply referred to as “solid electrolyte”) according to the present embodiment includes a sulfide glass phase.
[0042] The sulfide solid electrolyte contains PS4 units and P2S7 units. The peak intensity of the PS4 unit in the Raman spectrum is (PS4) The peak intensity of the P2S7 unit I (P2S7) The ratio satisfies 0.05<{I (P2S7) / I (PS4)}<1.00.
[0043] The sulfide solid electrolyte contains Li, P, S and Ha as constituent elements, Ha being a halogen element. The contents of Li, P and S expressed in at% are 30 to 50% for Li, 5 to 15% for P and 30 to 60% for S.
[0044] PS4 unit refers to the unit taken by PS4 3- The PS4 tetrahedral unit of the Q0 structure is shown in Figure 1. The PS4 unit has a wave number of 415-425 cm in the Raman spectrum. -1 There are peaks.
[0045] P2S7 unit refers to the unit taken by P2S7 4- The Q1 structure is represented by a dimer unit consisting of two PS4 tetrahedra connected together. The P2S7 unit has a wave number of 402-412 cm in the Raman spectrum. -1 There are peaks.
[0046] Sulfide solid electrolytes form a lithium ion conduction path by including PS4 units and expand the range of vitrification by including P2S7 units.
[0047] According to the research conducted by the present inventors, it is known that by mainly including PS4 units relative to P2S7 units in a specific composition containing Ha in addition to Li, P, and S, high lithium ion conductivity can be achieved even in a solid electrolyte containing sulfide glass.
[0048] The peak intensity I of the PS4 unit in the Raman spectrum is mainly composed of the PS4 unit relative to the P2S7 unit. (PS4)The peak intensity of the P2S7 unit I (P2S7) The ratio satisfies 0.05<{I (P2S7) / I (PS4)}<1.00.
[0049] It should be noted that the sulfide glass phase contained in the solid electrolyte involved in the present embodiment mainly contains PS4 units relative to the P2S7 units in a specific composition containing Ha in addition to Li, P, and S, thereby achieving the effect of the present invention. However, as described later, the solid electrolyte may be composed only of a sulfide glass phase, or may contain a crystalline phase in addition to the sulfide glass phase. In the case where the solid electrolyte contains a crystalline phase, it is impossible to distinguish between the P2S7 unit or PS4 unit constituting the glass phase and the P2S7 unit or PS4 unit constituting the crystalline phase. Therefore, the solid electrolyte is a specific composition containing Ha in addition to Li, P, and S. It can be considered that if it mainly contains PS4 units relative to the P2S7 unit, the sulfide glass phase is also the same composition and mainly contains PS4 units relative to the P2S7 unit.
[0050] By making {I (P2S7) / I (PS4) When the ratio represented by} is greater than 0.05, the effect of vitrification based on the P2S7 unit is easily obtained, and the sulfide glass phase is easily obtained. That is, the sulfide glass phase can be obtained at an appropriate rapid cooling rate, so it is preferred from the perspective of not requiring large-scale equipment for rapid cooling. In addition, when the solid electrolyte involved in this embodiment is mass-produced by the melt rapid cooling method described later, the obtained sulfide glass phase can contain the P2S7 unit.
[0051] On the other hand, by making {I (P2S7) / I (PS4) The ratio represented by} is less than 1.00, which can well form a lithium ion conduction path based on the PS4 unit and achieve high lithium ion conductivity.
[0052] The above ratio can be achieved, for example, by melting the raw material mixture while suppressing the volatilization of raw materials represented by P, and rapidly cooling the mixture at a cooling rate faster than conventional methods when obtaining a sulfide solid electrolyte.
[0053] {I (P2S7) / I (PS4) The ratio represented by} is greater than 0.05 and less than 1.00, preferably 0.1 to 0.9, and more preferably 0.12 to 0.7. Here, the lower limit of the above ratio is greater than 0.05, preferably greater than 0.1, and more preferably greater than 0.12. The upper limit of the above ratio is less than 1.00, preferably less than 0.9, and more preferably less than 0.7.
[0054] Peak intensity I in Raman spectra of PS4 unit and P2S7 unit (PS4) ,I (P2S7) The method to calculate is as follows.
[0055] First, the sulfide solid electrolyte is pulverized in a mortar and passed through a 100 μm sieve to obtain a solid electrolyte powder having an average particle size D50 of about 20 μm. It should be noted that in this specification, the average particle size D50 refers to the median particle size at which 50% by volume of the particles are smaller than this value, as determined from a volume-based particle size distribution diagram obtained by measuring the particle size distribution using a particle size distribution meter using a laser diffraction method.
[0056] The obtained solid electrolyte powder was formed into a granular pressed powder body, and Raman spectra were measured at any 10 points in an atmosphere non-exposed environment. The measurement conditions were as follows: excitation wavelength: 532nm, sample irradiation power: 5mW, objective lens: 10 times, numerical aperture: 0.25, confocal pinhole: 200μm, grating: 1200gr / mm, measurement time: 3 seconds × 10 times, spot diameter: 3μm.
[0057] The corrected spectrum is obtained after baseline correction of the obtained spectrum. The corrected spectrum is peak separated using a function that mixes Gaussian function and Lorentz function. The mixed function refers to the use of Gaussian function and Lorentz function,
[0058] It is expressed as f(x) = (1-M)(Gaussian function) + (M)(Lorentz function),
[0059] The value of M, which represents the mixing ratio of the function (% Lorentz function), is 0.25.
[0060] The baseline for peak separation is at 330 cm -1 ~460cm -1 Then, for wave numbers 415 to 425 cm -1 The peak with peak top has the full width at half maximum fixed at 15cm -1 , for wave numbers 402 to 412 cm -1 The peak with peak top has the full width at half maximum fixed at 15cm -1 , for wave numbers 383 to 393 cm -1 The peak with peak top has a fixed full width at half maximum of 22cm -1 , and separation is performed. Then, the least square method is used for optimization to minimize the difference between the spectrum obtained by subtracting the baseline and the calculated spectrum obtained by adding the peak separated peak. It should be noted that the value of the half-maximum full width is fixed to the above value in the measurement system this time, but it can also be analyzed based on the change of the spectrum.
[0061] After peak separation, the peaks will be at wave numbers 415-425 cm -1The peak with the peak top is set as the peak of the PS4 unit, and the peak with the peak top is set at 402-412 cm -1 The peak having a peak top was set as the peak of the P2S7 unit.
[0062] The peak intensity of each peak refers to the intensity at the top of the peak, that is, the highest intensity of each peak is used.
[0063] The sulfide solid electrolyte according to the present embodiment may further include a P2S6 unit. The P2S6 unit refers to a solid electrolyte composed of P2S6. 4- The P2S6 unit has a S-deficient structure. The P2S6 unit has a S-deficient structure at wave numbers 383 to 393 cm in the Raman spectrum. -1 There are peaks.
[0064] In the case where the sulfide solid electrolyte contains a P2S6 unit, the peak intensity I of the P2S6 unit in the Raman spectrum is (P2S6) The peak intensity of the P2S7 unit I (P2S7) The ratio of (P2S7) / I (P2S6)} is preferably greater than 0.5 and less than 10, more preferably 1.0 to 9.0, and further preferably 1.5 to 8.0. Here, the P2S6 unit is a unit that reduces lithium ion conductivity, so the above ratio is preferably greater than 0.5, more preferably greater than 1.0, and further preferably greater than 1.5. In addition, the P2S6 unit is also a unit that promotes vitrification, so the above ratio is preferably less than 10, more preferably less than 9.0, and further preferably less than 8.0.
[0065] The above ratio can be achieved, for example, by melting the raw material mixture while suppressing the volatilization of raw materials represented by P when obtaining the sulfide solid electrolyte, and rapidly cooling the mixture at a cooling rate faster than before.
[0066] The sulfide solid electrolyte according to the present embodiment preferably has a Raman spectrum at a wave number of 150 to 180 cm -1 The region has a peak, and the full width at half maximum of the peak is more preferably 20 cm -1 above.
[0067] The details of this peak are not yet clear, but as shown in the examples described below, for the peaks at wave numbers 150 to 180 cm -1 The area has a full width at half maximum of 20 cm -1 A solid electrolyte having a peak of 22 cm or more can obtain a result of high lithium ion conductivity. In addition, for a sulfide solid electrolyte having a large proportion of the sulfide glass phase, a strong broad peak is observed. The above-mentioned half-peak full width is more preferably 22 cm -1 More than 25 cm, more preferably -1 The upper limit of the half-maximum width is not particularly limited as long as it can be identified as a peak, and is, for example, 50 cm-1 the following.
[0068] The full width at half maximum in the Raman spectrum is an indicator of the extent of peak expansion, indicating the width between wave numbers of half the intensity of the peak top. The wider the full width at half maximum, i.e., the wider the peak, the lower the crystallinity, indicating a higher proportion of the sulfide glass phase.
[0069] Elements constituting the sulfide solid electrolyte according to the present embodiment include Li, P, S, and Ha. Ha is a halogen element, and only one type may be contained, or two or more types may be contained.
[0070] Specifically, the contents of the constituent elements expressed in at% satisfy Li: 30-50%, P: 5-15%, and S: 30-60%, preferably Li: 30-50%, P: 5-12%, S: 30-50%, and Ha: 2-10%.
[0071] Each constituent element is described below.
[0072] P is an element that forms a glass network, and the P-S bond in sulfide has high resistance to both oxidation and reduction. Therefore, as a solid electrolyte, it has a wide potential window and excellent electrochemical stability. The P content is expressed in at% as 5-15%, preferably 6-13%, and more preferably 7-12%. From the viewpoint of expanding the glass transition range, the P content is 5% or more, preferably 6% or more, and more preferably 7% or more. In addition, from the viewpoint of improving lithium ion conductivity, the P content is 15% or less, preferably 13% or less, and more preferably 12% or less.
[0073] Li is an element responsible for ion conduction as a solid electrolyte. The content of Li is 30 to 50% expressed in at%, preferably 35 to 45%, and more preferably 37 to 43%. From the viewpoint of improving lithium ion conductivity, the content of Li is 30% or more, preferably 35% or more, and more preferably 37% or more. In addition, from the viewpoint of expanding the glass transition range, the content of Li is 50% or less, preferably 45% or less, and more preferably 43% or less.
[0074] S is an element that forms a P-S bond together with P and is an element necessary for forming a glass phase. The S content is 30 to 60% expressed in at%, preferably 33 to 50%, and more preferably 35 to 47%. From the viewpoint of expanding the glass transition range, the S content is 30% or more, preferably 33% or more, and more preferably 35% or more. In addition, from the viewpoint of improving lithium ion conductivity, the S content is 60% or less, preferably 50% or less, and more preferably 47% or less.
[0075] Ha is an element necessary for forming sulfide glass with high lithium ion conductivity. As Ha, at least one selected from F, Cl, Br and I is preferably contained, and at least one selected from Cl, Br and I is more preferably contained.
[0076] The total content of Ha is preferably 2 to 10% in at%, more preferably 3 to 9%, and further preferably 3.5 to 8%. From the viewpoint of obtaining high lithium ion conductivity, the total content of Ha is preferably 2% or more, more preferably 3% or more, and further preferably 3.5% or more. In addition, from the viewpoint of preventing crystal precipitation of lithium halide, the total content of Ha is preferably 10% or less, more preferably 9% or less, and further preferably 8% or less.
[0077] Among the above-mentioned constituent elements, the ratio of the content of Li to P expressed in at% (Li / P) is preferably 2.5 to 7, more preferably 3.0 to 6.5, and further preferably 3.2 to 6.2. From the viewpoint of relatively increasing the PS4 unit and obtaining a high lithium ion conductivity, the above-mentioned ratio is preferably 2.5 or more, more preferably 3.0 or more, and further preferably 3.2 or more. In addition, from the viewpoint of expanding the glass transition range, the above-mentioned ratio is preferably 7 or less, more preferably 6.5 or less, and further preferably 6.2 or less.
[0078] The sulfide solid electrolyte according to the present embodiment may contain other elements other than the above-mentioned Li, P, S and Ha as constituent elements. Examples of other elements that may be contained include Si, B, Ge, Al, O, Na, K, Mg, Ca, Sr, Ba, Y, Zr, Cr, Zn, Ga, Sn, and Sb.
[0079] However, when the above-mentioned other elements constitute oxides such as SiO2, B2O3, P2O5, and Al2O3, since the oxides will become crystal nuclei, it is preferably not contained. The total content of the oxides is preferably 1 mol% or less, more preferably 0.1 mol% or less, and further preferably 0.05 mol% or less, expressed as mol% based on the oxide. It may also be not contained, that is, 0 mol%.
[0080] On the other hand, among the oxides, there are also oxides such as SiO2, B2O3, P2O5, Al2O3, etc., which are network formers of glass. When the content of these oxides is above a certain level, they have the effect of promoting the glass transition tendency of the obtained solid electrolyte. Therefore, in the case of oxides that form the network former of the above-mentioned glass, their total content is preferably 3 to 20 mol%, more preferably 5 to 18 mol%, and further preferably 7 to 16 mol% expressed as mol% of the oxide basis. Here, from the viewpoint of promoting the glass transition tendency, the above-mentioned total content is preferably 3 mol% or more, more preferably 5 mol% or more, and further preferably 7 mol% or more. In addition, from the viewpoint of achieving high lithium ion conductivity, the above-mentioned total content is preferably 20 mol% or less, more preferably 18 mol% or less, and further preferably 16 mol% or less.
[0081] When the sulfide solid electrolyte contains Si as a constituent element, the content thereof is preferably 0 to 15% in at%, more preferably 0 to 10%, and further preferably 0 to 5%. Here, from the viewpoint of increasing the viscosity of the melt and promoting the vitrification effect, the Si content may be contained, but from the viewpoint of electrochemical stability, the Si content is preferably 15% or less, more preferably 10% or less, and further preferably 5% or less.
[0082] Among them, when Si has a Si-O bond or is contained as an oxide of SiO2, as described above, the Si content expressed in at% is appropriately adjusted in a manner such that the total content of the oxides is less than 1 mol% or in a manner such that the total content of the oxides forming a network former of the glass is 3 to 20 mol%.
[0083] When the sulfide solid electrolyte contains B as a constituent element, the content thereof is preferably 0 to 15% in at%, more preferably 0 to 10%, and further preferably 0 to 5%. Here, from the viewpoint of increasing the viscosity of the melt and promoting the vitrification effect, the content of B may be contained, but from the viewpoint of lithium ion conductivity, the content of B is preferably 15% or less, more preferably 10% or less, and further preferably 5% or less.
[0084] When B has a B—O bond or is contained as an oxide of B 2 O 3 , the content of B expressed in at % is appropriately adjusted so that the total content of the oxides is 1 mol % or less, or so that the total content of the oxides forming a network former of the glass is 3 to 20 mol %, as described above.
[0085] When the sulfide solid electrolyte contains P as a constituent element, it basically exists in the state of P-S bonds, but it can also contain a part of P-O bonds. Although the effect of P-O as a crystal nucleus is not yet clear, it can become a network former of glass. As mentioned above, the content of P expressed in at% is 5 to 15%, and a part of it can also form P-O bonds.
[0086] The ratio of P forming P-O bonds to the total content of P is preferably 0 to 5% or 15 to 50%, more preferably greater than 0% and less than 4% or 15 to 40%, and further preferably 0.01 to 2% or 15 to 30%. Here, the smaller the ratio of P forming P-O bonds, the better, because it is avoided to form a crystal nucleus, but its content is preferably 0 to 5% within the industrially achievable range, and from the same point of view, it is more preferably greater than 0%, and further preferably 0.01% or more. In addition, from the viewpoint of avoiding forming a crystal nucleus, the above content is more preferably less than 4%, and further preferably less than 2%. From the viewpoint of becoming a network former and promoting vitrification, the above P ratio is preferably more than 15%. In addition, from the viewpoint of lithium ion conductivity, the above P ratio is preferably less than 50%, more preferably less than 40%, and further preferably less than 30%. It should be noted that the ratio of P forming P-O bonds to the total content of P can be obtained by 31 P-NMR was used to determine the results.
[0087] When the sulfide solid electrolyte contains Al as a constituent element, the content thereof is preferably 0 to 15% in at%, more preferably 0 to 10%, and further preferably 0 to 5%. Here, from the viewpoint of increasing the viscosity of the melt and promoting the vitrification effect, the Al content may be contained, but from the viewpoint of lithium ion conductivity, the Al content is preferably 15% or less, more preferably 10% or less, and further preferably 5% or less.
[0088] Among them, when Al has an Al-O bond or is contained as an oxide of Al2O3, as described above, the Al content expressed in at% is appropriately adjusted in a manner such that the total content of the oxides is less than 1 mol% or in a manner such that the total content of the oxides that become a network former of the glass is 3 to 20 mol%.
[0089] When the sulfide solid electrolyte contains O as a constituent element, the total content of oxides is preferably 1 mol % or less, or the total content of oxides forming a glass network former is preferably 3 to 20 mol %.
[0090] Therefore, the content of O expressed in at% varies depending on the types of other constituent elements, but is preferably 1% or less, more preferably 0.5% or less, and further preferably 0.1% or less from the viewpoint of suppressing the formation of crystals with oxides as nuclei. The lower the content of O, the better, and it may be non-existent, that is, 0%.
[0091] On the other hand, the content of O expressed in at% varies depending on the types of other constituent elements, but is preferably 3 to 15%, more preferably 4 to 10%, and further preferably 5 to 8% when serving as a network former of glass. Here, from the viewpoint of promoting vitrification, the content of O is preferably 3% or more, more preferably 4% or more, and further preferably 5% or more. On the other hand, from the viewpoint of lithium ion conductivity, the content of O is preferably 15% or less, more preferably 10% or less, and further preferably 8% or less.
[0092] When the sulfide solid electrolyte contains Zr as a constituent element, the content thereof is preferably 0 to 15% in at%, more preferably 0 to 10%, and further preferably 0 to 5%. Here, from the viewpoint of increasing the viscosity of the melt and promoting the vitrification effect, the Zr content may be contained, but from the viewpoint of lithium ion conductivity, the Zr content is preferably 15% or less, more preferably 10% or less, and further preferably 5% or less.
[0093] However, although Zr does not form a network former of glass, it has the effect of increasing the viscosity of the melt and promoting vitrification when it has a Zr-O bond or is contained as an oxide of ZrO2. From the above viewpoint, the content of Zr expressed in at% is appropriately adjusted so that the total content of the oxides is 3 to 20 mol%. Alternatively, as described above, in order to prevent the formation of crystal nuclei, the content of Zr expressed in at% is appropriately adjusted so that the total content of the oxides is less than 1 mol%.
[0094] The above-mentioned other elements, such as Sn, Sb, etc., are similar to Zr, and their total content is preferably 0 to 15% in at%, more preferably 0 to 10%, and further preferably 0 to 5%. Here, for example, from the viewpoint of increasing the viscosity of the melt to promote vitrification, other elements such as Sn and Sb may be contained, but from the viewpoint of lithium ion conductivity, the above-mentioned total content is preferably 15% or less, more preferably 10% or less, and further preferably 5% or less.
[0095] However, when other elements have a bond with O or are contained as oxides, the viscosity of the melt is increased and the vitrification is promoted. From the above viewpoint, the total content of other elements when contained is preferably 3% or more, more preferably 5% or more, and further preferably 8% or more. The total content of other elements expressed in at% is appropriately adjusted so that the total content of oxides is 3 to 20 mol%. Alternatively, as described above, in order to prevent oxides from becoming crystal nuclei, other elements may be substantially not contained, for example, 1 at% or less.
[0096] As described above, the sulfide glass phase contains Li, P, S and Ha as constituent elements in a specific range, and mainly includes PS4 units relative to P2S7 units.
[0097] From the viewpoints of contact between electrolytes, contact between electrolytes and active materials, and composition uniformity, the content of the sulfide glass phase in the solid electrolyte is preferably 50% by weight or more, more preferably 70% by weight or more, and even more preferably 80% by weight or more. It may also be 100% by weight, that is, it may be composed only of the sulfide glass phase. On the other hand, from the viewpoint of reducing the manufacturing load and promoting the crystallization rate of the subsequent process, a crystalline phase may be contained. In this case, the content of the sulfide glass phase is preferably 99% by weight or less, more preferably 95% by weight or less, and even more preferably 90% by weight or less. As one aspect of the content of the sulfide glass phase, 50 to 100% by weight can be cited, as one aspect, 70 to 99% by weight can be cited, and as one aspect, 80 to 95% by weight can be cited.
[0098] The content of the sulfide glass phase can be determined by powdering the obtained electrolyte, performing powder X-ray diffraction (XRD) measurement together with a crystal powder as an internal standard, and performing Rietveld analysis.
[0099] The sulfide solid electrolyte involved in this embodiment is suitable as an electrolyte for lithium ion secondary batteries. In addition, the sulfide solid electrolyte involved in this embodiment has a wide potential window and is difficult to oxidatively decompose even on the high potential side. Therefore, it is also preferably used together with a positive electrode with an operating potential of about 4V, which is called a 4V-class positive electrode, and a positive electrode with an operating potential of about 5V, which is called a 5V-class positive electrode.
[0100] The lithium ion conductivity of the sulfide solid electrolyte according to the present embodiment is preferably greater than 1.0×10 -4 S / cm, more preferably 3.0×10 -4 S / cm or more, more preferably 5.0×10 -4 S / cm or more.
[0101] It should be noted that the lithium ion conductivity in this specification refers to the value measured by the following method. First, the sulfide solid electrolyte is crushed in a mortar and passed through a 100μm sieve to obtain a solid electrolyte powder with an average particle size D50 of about 20μm. The obtained solid electrolyte powder is pressed into a powder body with a pressure of 380kN as a measurement sample. The AC impedance measurement of the measurement sample is performed using an AC impedance measurement device with a measurement frequency of 100Hz to 1MHz, a measurement voltage of 100mV, and a measurement temperature of 25°C. The value obtained from the obtained Nyquist plot is used as the lithium ion conductivity.
[0102] When used in a lithium ion secondary battery, the sulfide solid electrolyte forms a solid electrolyte layer together with other components such as a binder as necessary. Conventionally known substances can be used as the binder and other components.
[0103] The content of the solid electrolyte is preferably 80% by mass or more, more preferably 90% by mass or more, based on the entire solid electrolyte layer.
[0104] The solid electrolyte can be mixed with a positive electrode active material or a negative electrode active material to be used as a positive electrode layer or a negative electrode layer. The positive electrode active material or negative electrode active material, current collector, binder, conductive additive, etc. used in the positive electrode layer or the negative electrode layer can use conventionally known materials.
[0105] A lithium ion secondary battery using a solid electrolyte includes the above-described solid electrolyte layer, a positive electrode layer, and a negative electrode layer.
[0106] The material of the outer package of the lithium ion secondary battery can also use the material known in the past. The shape of the lithium ion secondary battery can also use the shape known in the past, for example, coin-shaped, sheet-shaped (membrane-shaped), folded, wound-type bottomed cylindrical, button-shaped, etc. can be cited, and can be appropriately selected according to the purpose.
[0107] <Method for producing sulfide solid electrolyte>
[0108] The method for producing the sulfide solid electrolyte involved in the present embodiment is not particularly limited as long as the solid electrolyte described in the above <Sulfide solid electrolyte> can be obtained. On the other hand, in the past, it was difficult to obtain a sulfide solid electrolyte containing a sulfide glass phase, and it was mainly composed of PS4 units relative to P2S7 units. In particular, in a system containing halogen elements as elements constituting the sulfide solid electrolyte, a method for obtaining a sulfide solid electrolyte containing a sulfide glass phase mainly containing PS4 units is unclear.
[0109] In contrast, the present inventors have discovered that, as one method of manufacturing, by rapidly cooling the melt of the raw material mixture after obtaining it, a solid electrolyte of uniform sulfide glass mainly comprising PS4 units can be obtained even when a halogen element is contained, and high lithium ion conductivity can be achieved.
[0110] That is, as one aspect of the method for producing a sulfide solid electrolyte according to the present embodiment, the production method i includes the following steps 1 to 3 in order.
[0111] Step 1: A step of mixing raw materials containing lithium element, sulfur element, and phosphorus element to obtain a raw material mixture.
[0112] Step 2: A step of heating and melting the raw material mixture in a gas atmosphere containing sulfur element to obtain a molten product.
[0113] Step 3: A step of rapidly cooling the melt to obtain a solid.
[0114] The ratio of the content of the lithium element to the phosphorus element in the raw material mixture obtained in step 1 expressed in at% is Li / P ≥ 2.5.
[0115] In addition, the cooling rate of the rapid cooling in step 3 is 500° C. / sec or more.
[0116] That is, Figure 1 As shown, as step S1, process 1 is a process of mixing raw materials, as step S2, process 2 is a process of heating and melting the raw material mixture obtained in process 1, and as step S3, process 3 is a process of rapidly cooling the melt obtained in process 2.
[0117] In step 1, it is preferred that a raw material further containing a halogen element is included. That is, step 1 in production method i is preferably the following step 1'.
[0118] Step 1': a step of mixing raw materials containing lithium element, sulfur element, phosphorus element and halogen element to obtain a raw material mixture.
[0119] As one embodiment of the production method i, there can be mentioned a production method a which includes the following steps a1-1, a1-2, a2, and a3 in order.
[0120] Step a1-1: A step of mixing raw materials containing lithium element, sulfur element, and phosphorus element to obtain a raw material mixture.
[0121] Step a1-2: a step of heat-treating the above-mentioned raw material mixture to obtain an intermediate.
[0122] Step a2: a step of heating and melting the intermediate in a gas atmosphere containing sulfur element to obtain a molten product.
[0123] Step a3: a step of rapidly cooling the melt to obtain a solid.
[0124] Here, the raw materials are mixed so that the ratio of the content of lithium element and phosphorus element expressed in at% in the raw material mixture obtained in step a1-1 is Li / P ≥ 2.5. In addition, the cooling rate of the rapid cooling in the above step a3 is 500°C / sec or more.
[0125] As one embodiment of the production method a, in the mixing of raw materials in step a1-1, a raw material containing a halogen element is further mixed to obtain the raw material mixture, or in step a2, a raw material containing a halogen element is mixed with the intermediate and then heated and melted to obtain the molten product.
[0126] In addition, as one embodiment of the above-mentioned production method i, there can be mentioned a production method b which includes the following steps b1-1, b1-2, b2 and b3 in order.
[0127] Step b1-1: A step of mixing raw materials containing lithium element, sulfur element, and phosphorus element to obtain a raw material mixture.
[0128] Step b1-2: a step of sealing the raw material mixture in a sealed container.
[0129] Step b2: a step of heating the sealed container to obtain a molten product by heating and melting the raw material mixture.
[0130] Step b3: A step of taking out the melt from the sealed container and rapidly cooling the melt to obtain a solid.
[0131] Here, the raw materials are mixed so that the content ratio of lithium element to phosphorus element expressed in at% in the raw material mixture obtained in step b1-1 is Li / P ≥ 2.5. In addition, the cooling rate of the rapid cooling in the above step b3 is 500°C / sec or more.
[0132] As one embodiment of the production method b, in the mixing of the raw materials in step b1-1, a raw material containing a halogen element is further mixed to obtain the raw material mixture.
[0133] The details of the above-mentioned production method i will be described in detail using production method a and production method b.
[0134] 《Manufacturing method a》
[0135] Process a1
[0136] like Figure 2 As shown, step a1-1 in the manufacturing method a is a step of mixing raw materials as step S11a. Specifically, raw materials containing lithium, sulfur and phosphorus are mixed to obtain a raw material mixture. In addition to the above, it is also preferred to mix raw materials containing halogen elements to obtain a raw material mixture.
[0137] When a raw material containing a halogen element is used, the raw material containing a halogen element may not react when an intermediate is obtained by heat treatment in the subsequent step a1-2 and may be contained in the intermediate in its original state. Therefore, in the manufacturing method according to the present embodiment, after the intermediate is obtained by heat treatment in the subsequent step a1-2, the raw material containing a halogen element is mixed with the intermediate to obtain a melt based on the heating and melting in step a2.
[0138] As such raw materials, in addition to Li simple substance, compounds containing Li, S simple substance, compounds containing S, and P simple substance, compounds containing P, compounds containing Ha, etc. can be used in combination as desired. The above-mentioned compounds may also contain two or more compounds selected from Li, S, P and Ha. For example, as a compound that serves as both a compound containing S and a compound containing P, phosphorus pentasulfide (P2S5) and the like can be cited. In addition, as a compound that serves as both a compound containing Li and a compound containing Ha, lithium halide can be cited.
[0139] As raw materials containing the Li element, in addition to metallic lithium, compounds containing Li include lithium compounds such as lithium sulfide (Li2S), lithium carbonate (Li2CO3), lithium sulfate (Li2SO4), lithium oxide (Li2O) and lithium hydroxide (LiOH).
[0140] From the viewpoint of the ease of synthesis and operation of the intermediate described later, the raw material containing the Li element is preferably lithium sulfide. On the other hand, since lithium sulfide is expensive, lithium compounds other than lithium sulfide, metallic lithium, etc. are preferred from the viewpoint of suppressing manufacturing costs. Specifically, it is preferred to use one or more selected from metallic lithium, lithium carbonate (Li2CO3), lithium sulfate (Li2SO4), lithium oxide (Li2O) and lithium hydroxide (LiOH). These can be used alone or in combination of two or more.
[0141] As raw materials containing the sulfur element, in addition to elemental sulfur, compounds containing sulfur include phosphorus sulfide such as phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5), other sulfur compounds containing phosphorus, and compounds containing sulfur. Examples of compounds containing sulfur include H2S, CS2, FeS, Fe2S3, FeS2, Fe 1-x S and other iron sulfides, bismuth sulfide (Bi2S3), CuS, Cu2S, Cu 1-x S and other copper sulfides, etc.
[0142] From the viewpoint of the ease of reaction during the synthesis of the intermediate described later and the prevention of the inclusion of elements other than the elements constituting the target sulfide solid electrolyte, the raw material containing the S element is preferably phosphorus sulfide, and more preferably phosphorus pentasulfide (P2S5). These can be used alone or in combination of two or more. It should be noted that phosphorus sulfide is considered to be a compound that serves as both a substance containing S and a substance containing P.
[0143] As raw materials containing the P element, in addition to elemental phosphorus, compounds containing P include phosphorus sulfides such as phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5), lithium thiophosphate (Li3PS 4-x O x ) and other phosphorus compounds.
[0144] From the viewpoint of the ease of reaction during the synthesis of the intermediate described later and the prevention of the inclusion of elements other than the elements constituting the target sulfide solid electrolyte, the raw material containing the P element is preferably phosphorus sulfide, more preferably phosphorus pentasulfide (P2S5). These may be used alone or in combination of two or more.
[0145] In addition, as a raw material containing the P element, when an oxide is contained, for example, P2O5, Li3PO4, Li4P2O7, etc. can be cited. Among them, P2O5 is preferred from the viewpoint of ease of production. These compounds can be used alone or in combination of two or more.
[0146] Examples of Ha-containing compounds that are raw materials containing the Ha element include lithium halides such as lithium fluoride (LiF), lithium chloride (LiCl), lithium bromide (LiBr), and lithium iodide (LiI), phosphorus halides, phosphoryl halides, sulfur halides, sodium halides, and boron halides.
[0147] From the viewpoint of preventing the inclusion of elements other than the elements constituting the target sulfide solid electrolyte, the raw material containing the Ha element is preferably a lithium halide, more preferably LiCl, LiBr, or LiI. These compounds may be used alone or in combination of two or more.
[0148] In addition, the lithium halide may be a compound containing Li. When the raw material contains the lithium halide, a part or all of the Li in the raw material may be derived from the lithium halide.
[0149] When the raw material contains a halogen element, the molar equivalent of Ha in the raw material relative to P is preferably 0.1 to 4 molar equivalents, and more preferably 0.2 to 3 molar equivalents. Here, from the viewpoint of lowering the melting point when heating the molten intermediate, the molar equivalent of Ha is preferably 0.1 molar equivalent or more, and more preferably 0.2 molar equivalent or more. In addition, from the viewpoint of the stability of the obtained sulfide solid electrolyte, the molar equivalent of Ha is preferably 4 molar equivalents or less, and more preferably 3 molar equivalents or less.
[0150] When other elements other than Li, S, P and Ha are contained as elements constituting the sulfide solid electrolyte, raw materials containing the other elements are mixed to obtain a raw material mixture.
[0151] It should be noted that the raw materials containing these other elements can be mixed together to obtain a raw material mixture when mixing the raw materials in step a1-1, similarly to the raw materials containing the Ha element, or can be mixed with the intermediate in step a2 and melted together with the intermediate to obtain a melt.
[0152] The above-mentioned raw materials containing other elements are explained.
[0153] Examples of raw materials containing Si element include SiO 2 and SiS 2. Among them, SiO 2 is more preferred from the viewpoint of lithium ion conductivity and water resistance. These compounds may be used alone or in combination of two or more.
[0154] Examples of the raw material containing the B element include B2O3 and B2S3. Among them, B2O3 is more preferred from the viewpoint of water resistance of the glass. These compounds may be used alone or in combination of two or more.
[0155] Examples of raw materials containing the Al element include Al2S3, Al2O3, and AlCl3. Among them, from the viewpoint of lithium ion conductivity and water resistance, Al2S3 and AlCl3 are preferred, and Al2S3 is more preferred. These compounds may be used alone or in combination of two or more.
[0156] As the raw material containing the O element, the oxides of the above-mentioned elements can be cited. Among them, the oxides of the elements that form the network former of the glass are preferred, for example, preferably SiO2, B2O3, P2O5, Al2O3, more preferably SiO2. These compounds can be used alone or in combination of two or more.
[0157] The raw materials can be mixed by, for example, mixing in a mortar, mixing using a medium such as a planetary ball mill, or mixing without a medium such as a pin mill, a powder mixer, or air flow mixing. The raw materials may also be amorphized by mixing before heating.
[0158] The ratio of the mixed raw materials is appropriately adjusted according to the target composition of the sulfide solid electrolyte or the intermediate.
[0159] Therefore, the mixing ratio of the raw materials is not particularly limited. For example, the ratio of Li to P in the raw materials, i.e., Li / P, is 2.5 or more, preferably 2.5 to 7, more preferably 3.0 to 6.5, and further preferably 3.2 to 6.2. Here, from the viewpoint of synthesizing the target intermediate with high precision and relatively increasing the PS4 unit in the obtained sulfide solid electrolyte to obtain high lithium ion conductivity, Li / P is 2.5 or more, preferably 3.0 or more, and further preferably 3.2 or more. In addition, from the viewpoint of expanding the glass transition range, the above ratio is preferably 7 or less, more preferably 6.5 or less, and further preferably 6.2 or less.
[0160] As an example of a preferred combination of the above compounds, a combination of Li2S and P2S5 can be cited. In the case of combining Li2S and P2S5, by making the molar ratio of Li to P Li / P within the above range, it is easy to suppress the volatilization of sulfur and phosphorus components during heat treatment caused by the boiling point of P2S5 being lower than the melting point of Li2S.
[0161] From the viewpoint of the composition of the target sulfide solid electrolyte and the intermediate, the raw materials are preferably mixed so that the contents of each element are expressed in at% as Li: 30-50%, P: 5-15% and S: 30-60%, and more preferably Li: 30-50%, P: 5-12%, S: 30-50% and Ha: 2-10%.
[0162] From the perspective of shortening the holding time of the heat treatment in the subsequent step a1-2, that is, shortening the reaction time for synthesizing the intermediate, it is preferred to reduce the particle size of the raw material. In addition, if the particle size (D50) of the raw material is too large, it sometimes affects the uniformity of the sulfide solid electrolyte. From this perspective, it is preferably small to a certain extent. Among them, since the composition controllability of the present manufacturing method is excellent, for example, even if a raw material with a particle size that can reduce uniformity is used in a previous manufacturing method, the present manufacturing method can produce a more uniform sulfide solid electrolyte. From these viewpoints, specifically, the particle size (D50) of the raw material is preferably less than 1 mm, more preferably less than 500 μm, further preferably less than 250 μm, further preferably less than 100 μm, and particularly preferably less than 50 μm.
[0163] The smaller the particle size, the better, but the actual lower limit is about 0.1 μm, preferably 1 μm or more, and more preferably 5 μm or more. In addition, as described above, according to the present manufacturing method, it is easy to obtain a uniform sulfide solid electrolyte even if a raw material with a larger particle size is used. Taking these into consideration, for example, from the perspective of suppressing manufacturing costs, the particle size of the raw material is preferably 10 μm or more, more preferably 100 μm or more, and further preferably 250 μm or more.
[0164] Based on these, the particle size (D50) of the raw material is preferably 0.1 μm to 1 mm, more preferably 1 to 500 μm, further preferably 5 to 250 μm, further preferably 5 to 100 μm, and particularly preferably 5 to 50 μm. In addition, from the viewpoint of manufacturing cost, the particle size (D50) of the raw material is preferably 10 μm to 1 mm, more preferably 100 μm to 1 mm, and further preferably 250 to 500 μm.
[0165] It should be noted that the raw material may be a mixture of multiple compounds as described above. The raw material may also be a mixture of multiple substances with different particle sizes. In this case, the particle size of each substance is preferably within the above range.
[0166] In this specification, the particle size (D50) of the raw material is the median diameter (D50) obtained from a volume-based particle size distribution graph obtained by measuring the particle size distribution using a laser diffraction particle size distribution measuring apparatus MT3300EXII manufactured by Microtrac.
[0167] Process a1-2
[0168] like Figure 2 As shown, step a1-2 is a step of subjecting the raw material mixture obtained in step a1-1 to a heat treatment as step S11b to obtain an intermediate.
[0169] The specific method of heat treatment is not particularly limited, and for example, a method of adding the raw material mixture to a heat-resistant container and heating it in a heating furnace can be cited. The heat-resistant container is not particularly limited, and examples thereof include heat-resistant containers made of carbon, heat-resistant containers containing oxides such as quartz, quartz glass, borosilicate glass, aluminosilicate glass, aluminum oxide, zirconium oxide, and mullite, heat-resistant containers containing nitrides such as silicon nitride and boron nitride, and heat-resistant containers containing carbides such as silicon carbide. In addition, these heat-resistant containers may be a main body formed of the above-mentioned materials, or a container formed with a layer of oxides, nitrides, carbides, etc.
[0170] In the heat treatment, the temperature at which the raw material mixture is heated is preferably 250 to 500° C., more preferably 255 to 450° C., and further preferably 260 to 400° C. Here, from the viewpoint of facilitating the synthesis reaction for obtaining the intermediate, the temperature at which the raw material mixture is heated is preferably 250° C. or higher, more preferably 255° C. or higher, and further preferably 260° C. or higher. In addition, from the viewpoint of suppressing the volatilization of low-boiling-point components such as P2S5 in the raw materials and facilitating the reaction of synthesizing the intermediate containing the compound of the target composition, the temperature at which the raw material mixture is heated is preferably 500° C. or lower, more preferably 450° C. or lower, and further preferably 400° C. or lower.
[0171] In order to obtain an intermediate by heat treatment, it is preferred to maintain the temperature within the above preferred temperature range for a certain period of time. The temperature range during maintenance is more preferably within a certain temperature range, for example, preferably within ±15°C of the reference temperature, more preferably within ±10°C.
[0172] The holding time of the heat treatment is preferably 1 to 600 minutes, more preferably 5 to 600 minutes, further preferably 10 to 500 minutes, further preferably 15 to 500 minutes, and particularly preferably 20 to 500 minutes. Here, from the viewpoint of fully reacting to obtain the desired intermediate, the holding time is preferably more than 1 minute, more preferably more than 5 minutes, further preferably more than 10 minutes, further preferably more than 15 minutes, and particularly preferably more than 20 minutes. In addition, from the viewpoint of suppressing the volatilization of low-boiling-point components such as P2S5 in the raw materials, the above-mentioned holding time is preferably less than 600 minutes, and more preferably less than 500 minutes.
[0173] In the case of applying prescribed treatment to the raw materials, the above-mentioned holding time can sometimes be further shortened. As such treatment, for example, reducing the particle size of the raw materials, removing or modifying the oxide layer on the surface of the particles contained in the raw materials as much as possible by etching, making the particles porous, adjusting the mixing conditions of the raw materials, improving the uniformity of the raw materials, etc. can be cited. These can be used to improve the reactivity of the particles contained in the raw materials. In this case, the holding time is preferably 1 second to 10 minutes, more preferably 10 seconds to 10 minutes, and more preferably 20 seconds to 5 minutes. Here, from the viewpoint of fully reacting to obtain the desired intermediate, the lower limit of the holding time is preferably more than 1 second, more preferably more than 10 seconds, and more preferably more than 20 seconds. In addition, from the viewpoint of suppressing the volatilization of low-boiling components such as P2S5 in the raw materials, the holding time is preferably less than 10 minutes, and more preferably less than 5 minutes.
[0174] The pressure during the heat treatment is not particularly limited, but is preferably normal pressure to slightly increased pressure, and more preferably normal pressure.
[0175] For the heat treatment for synthesizing the intermediate, it is preferably carried out under an inert gas atmosphere in order to prevent side reactions between the raw material mixture and water vapor, oxygen, etc. Specifically, for example, N2 gas, argon gas, and helium gas can be cited. In addition, the dew point during the heat treatment is preferably below -20°C, and the lower limit is not particularly limited, usually about -80°C. The oxygen concentration is preferably below 1000ppm.
[0176] In the synthesis of the intermediate, by adjusting the compounds contained in the raw material mixture and their mixing ratio, and controlling the conditions during the heat treatment, intermediates of different compositions can be obtained according to the purpose. The intermediate obtained can be used for the heating and melting process directly in the heating furnace used for the synthesis of the intermediate without being taken out of the heat-resistant container, or it can be taken out and temporarily stored after cooling to room temperature. It is also possible to combine a plurality of intermediates of different compositions that are taken out and stored and use them in the heating and melting process. In the heating and melting process, by controlling the amount of sulfur introduced into the intermediate under a gas atmosphere containing sulfur element, it becomes easy to distinguish and produce sulfide solid electrolytes with different compositions, physical properties, and performances.
[0177] As an example of the composition of the intermediate obtained in this step, compounds containing Li, P and S such as Li4P2S6 and Li3PS4 can be cited. In the heating and melting step, from the viewpoint of controlling the amount of sulfur introduced into the intermediate under a gas atmosphere containing sulfur element, the intermediate preferably contains at least one of Li4P2S6 and Li3PS4. In addition, since Li4P2S6 and Li3PS4 are thermodynamically stable, they are also preferred from the viewpoint of stability during temporary storage of the intermediate.
[0178] Here, the reaction occurring in the synthesis of the intermediate also depends on the composition of the target sulfide solid electrolyte, but the typical reaction characteristic is that Li2S and P2S5 contained in the raw material start to react at about 250°C to form at least one of Li4P2S6 and Li3PS4. In addition, in this reaction, Li2S and P2S5 can start from the raw material containing Li and the raw material containing P obtained in the previous stage.
[0179] In order to accelerate the reaction in essence, as described above, it is preferred to increase the reactivity of the particles contained in the raw materials. In particular, in this reaction, the particle size of Li2S, which is the object of the initial reaction of P2S5, easily affects the synthesis reaction of the intermediate. Therefore, from the viewpoint of promoting the synthesis reaction of the intermediate, it is preferred to refine the particle size of the raw material containing Li in the previous stage of obtaining Li2S or Li2S. In addition, from the above viewpoint, it is also effective to reduce the crystallinity of the surface of Li2S, increase the surface area treatment other than micronization, etc. In addition, reacting Li2S with P2S5 in a gas atmosphere containing sulfur element helps to promote the synthesis reaction of the intermediate.
[0180] By obtaining the step a1-2 of the intermediate, the volatilization of the sulfur component and the phosphorus component in the raw material can be suppressed compared with the case where the target sulfide solid electrolyte is obtained directly from the raw material. Therefore, compounds with clear composition information containing Li, P and S, such as Li4P2S6 and Li3PS4, can be synthesized as intermediates. Since these intermediates are thermodynamically stable, they are cooled to room temperature and taken out after the heat treatment during the synthesis of the intermediate. The intermediate taken out in this way can also be analyzed for composition, so the amount of sulfur introduced in the heating and melting process can be known. In addition, by passing the raw material through an intermediate of a specific composition, it is easy to set the conditions for heating and melting more appropriately according to the composition of the intermediate. As a result, the amount of sulfur introduced can be appropriately controlled in a gas atmosphere containing sulfur elements, so it is not easy to cause composition deviation. Furthermore, by heating and melting after passing through an intermediate having a composition closer to the target sulfide solid electrolyte than the raw material, the composition of the obtained sulfide solid electrolyte can be made uniform. In addition, if a plurality of intermediates of different compositions are combined for heating and melting, it becomes easy to distinguish and produce sulfide solid electrolytes with different compositions, physical properties and performances.
[0181] Process a2
[0182] like Figure 2 As shown, step a2 is a step of heating and melting the intermediate obtained in step a1-2 in a gas atmosphere containing sulfur element as step S12 to obtain a molten product.
[0183] As described above, the intermediate to be heated and melted may be an intermediate composition in which a plurality of intermediates are mixed as necessary, or a raw material containing other elements such as a raw material containing a halogen element may be added to the intermediate and heated and melted.
[0184] It should be noted that in step 2 of manufacturing method i, the raw material mixture is heated and melted. However, when manufacturing method i adopts this manufacturing method a, the object of heating and melting is not the raw material mixture, but the intermediate obtained by heating the raw material mixture. In addition, as described above, an intermediate composition mixed with a plurality of intermediates, or an intermediate obtained by adding raw materials containing other elements to an intermediate can be used as the object of heating and melting.
[0185] The specific method of heating and melting is not particularly limited, and for example, a method of adding the intermediate to a heat-resistant container and heating it in a heating furnace can be cited. The heat-resistant container is not particularly limited, and examples thereof include heat-resistant containers made of carbon, heat-resistant containers containing oxides such as quartz, quartz glass, borosilicate glass, aluminosilicate glass, aluminum oxide, zirconium oxide, and mullite, heat-resistant containers containing nitrides such as silicon nitride and boron nitride, and heat-resistant containers containing carbides such as silicon carbide. In addition, these heat-resistant containers may be a main body formed of the above-mentioned materials, or may be a container formed with a layer of oxide, nitride, carbide, etc.
[0186] The heating and melting is performed in a gas atmosphere containing sulfur. The gas containing sulfur is, for example, a sulfur compound containing sulfur such as sulfur gas, hydrogen sulfide gas, carbon disulfide gas, or sulfur gas.
[0187] The gas containing sulfur element may be composed only of a gas compound containing sulfur element such as sulfur gas, hydrogen sulfide gas, carbon disulfide gas, etc., and preferably contains an inert gas such as N2 gas, argon gas, helium gas, etc. from the viewpoint of reducing costs and using it as a carrier gas for transporting sulfur components. In addition, the gas containing sulfur element may contain impurities derived from a sulfur source, etc., as long as the effect of the present production method is not impaired.
[0188] When the gas containing sulfur element contains sulfur gas, the sulfur gas (S x The content of sulfur gas (x=2~8)) is preferably 0.01~100 volume %, more preferably 0.1~99 volume %, and further preferably 0.2~98 volume %. Here, from the viewpoint of ensuring a sufficient amount of sulfur element and allowing the reaction of sulfur introduction to proceed, the content of sulfur gas is preferably 0.01 volume % or more, more preferably 0.1 volume % or more, and further preferably 0.2 volume % or more. In addition, although the content of sulfur gas is 100 volume % or less, from the viewpoint of suppressing costs and using an inert gas as a carrier, it is preferably 99 volume % or less, and more preferably 98 volume % or less. Sulfur gas (S x The content of (x=2 to 8)) can be measured by mass spectrometry gas chromatography.
[0189] The sulfur-containing gas can be obtained by heating a sulfur source. Therefore, the sulfur source is not particularly limited as long as it is simple sulfur or a sulfur compound that can obtain a sulfur-containing gas by heating. Examples thereof include simple sulfur, hydrogen sulfide, organic sulfur compounds such as carbon disulfide, FeS, Fe2S3, FeS2, Fe 1-x S and other iron sulfides, bismuth sulfide (Bi2S3), CuS, Cu2S, Cu 1-x Copper sulfide such as S, polysulfides such as lithium polysulfide and sodium polysulfide, polysulfides, rubber vulcanized with sulfur, etc.
[0190] For example, these sulfur sources are heated in a separately provided sulfur source heating section to generate a gas containing sulfur element, and an inert gas such as N2 gas, argon gas, helium gas, etc. is transported to a heating and melting furnace as a carrier gas, thereby obtaining a gas atmosphere containing sulfur element. By separating the sulfur source heating section from the section where the heating and melting process is performed, even if the gas introduced into the heating and melting furnace contains oxygen and water, it can be removed by reacting with the sulfur gas before introduction. In this way, a high-quality and high-purity sulfide solid electrolyte with few impurities can be obtained, which is preferred.
[0191] The temperature for heating the sulfur source may be appropriately selected depending on the type of sulfur source used. For example, when elemental sulfur is used as the sulfur source, the heating temperature is preferably 250° C. or higher and preferably 750° C. or lower.
[0192] Alternatively, a solid sulfur source such as elemental sulfur, H2S, Bi2S3, iron sulfide, copper sulfide, CS2, etc. among the above-mentioned sulfur sources may be transported to a heating melting furnace in a fine state such as powder by a carrier gas, thereby obtaining a gas atmosphere containing sulfur element.
[0193] The specific method for heating and melting the intermediate can be a conventionally known method, for example, a portion for heating the sulfur source to generate a gas containing sulfur element and a portion for supplying the gas containing sulfur element and heating and melting the intermediate can be separately provided. The sulfur component such as P2S5 volatilized in the synthesis reaction of the intermediate can be recovered and used as the sulfur source of this step a2.
[0194] By heating and melting the intermediate in a gas atmosphere containing elemental sulfur, sulfur is introduced into the melt of the intermediate, thereby introducing a sufficient amount of sulfur for obtaining a sulfide solid electrolyte of a target composition.
[0195] In addition, by introducing sulfur in a liquid phase state to melt the intermediate, the reaction time for sulfur introduction can be shortened compared to the reaction in a solid phase state. In addition, since it is in a liquid phase state, it is easy to introduce sulfur uniformly into the entire melt, and the composition of the obtained sulfide solid electrolyte is easy to become uniform. It should be noted that the viscosity of the melt of the intermediate decreases due to the fluidization of the solid, and it becomes a highly uniform state. As a result, the solubility and diffusivity of the gas containing sulfur element in the melt of the intermediate are large. Therefore, the effect of shortening the reaction time and homogenizing the composition brought about by the reaction in the liquid phase state is more excellent. In addition, if the melt and the gas containing sulfur element are heated and melted while stirring, it is easier to obtain the above-mentioned effect, so it is more preferred.
[0196] The heating and melting temperature is preferably 600 to 950° C., more preferably 630 to 900° C., and even more preferably 650 to 850° C. Here, from the viewpoint of improving the fluidity of the melt to advance the reaction of sulfur introduction, the heating and melting temperature is preferably 600° C. or higher, more preferably 630° C. or higher, and even more preferably 650° C. or higher. In addition, from the viewpoint of suppressing the degradation and decomposition of the components in the melt due to heating, the heating and melting temperature is preferably 950° C. or lower, more preferably 900° C. or lower, and even more preferably 850° C. or lower.
[0197] The heating and melting time is preferably 0.1 to 10 hours, more preferably 0.5 to 9.5 hours, further preferably 0.7 to 9 hours, and particularly preferably 1 to 9 hours. Here, from the viewpoint of advancing the reaction of sulfur introduction, the heating and melting time is preferably 0.1 hour or more, more preferably 0.5 hour or more, further preferably 0.7 hour or more, and further preferably 1 hour or more. In addition, from the viewpoint of suppressing the degradation and decomposition of the components in the melt due to heating, the heating and melting time is preferably 10 hours or less, more preferably 9.5 hours or less, and further preferably 9 hours or less.
[0198] Heating and melting can be performed as a continuous process. A continuous process refers to a process in which a molten melt flows continuously from a heat-resistant container. The input substance can be an intermediate or a raw material mixture. The input can be continuous or intermittent. In the case of heating and melting as a continuous process, the melt can be kept in a molten state for a long time under appropriate conditions that take into account the progress of the reaction of sulfur introduction and the degradation of the components in the melt. The long time can be, for example, about 24 hours.
[0199] The pressure during heating and melting is not particularly limited, but is preferably normal pressure to slightly increased pressure, and more preferably normal pressure. -3 ~10 0 By achieving this sulfur partial pressure, sulfur can be introduced efficiently at low cost without complicating the device, and the target sulfide solid electrolyte can be easily obtained.
[0200] When heated and melted, the dew point is preferably -20°C or lower from the viewpoint of preventing side reactions with water vapor, oxygen, etc. The lower limit is not particularly limited, but is usually about -80°C. The oxygen concentration is preferably 1000 ppm or lower.
[0201] Process a3
[0202] like Figure 2 As shown, step a3 is a step of rapidly cooling the melt obtained in step a2 at a cooling rate of 500° C. / sec or more as step S13 to obtain a solid.
[0203] The melt obtained by heating and melting is rapidly cooled at a cooling rate of 500°C / sec or more. As a result, the composition uniformity of the solid including the obtained sulfide glass phase is very high, and the quality deviation is well suppressed. In addition, a structure mainly including PS4 units can be realized relative to P2S7 units, and high lithium ion conductivity can be achieved.
[0204] The cooling rate may be 500°C / sec or more, preferably 500 to 1,000,000°C / sec, more preferably 700 to 100,000°C / sec, and further preferably 1,000 to 10,000°C / sec. Here, from the viewpoint of the uniformity of the composition of the obtained solid and the high lithium ion conductivity as a sulfide solid electrolyte, the cooling rate is 500°C / sec or more, preferably 700°C / sec or more, and more preferably 1,000°C / sec or more. In addition, considering the cooling rate of the twin rolls generally considered to have the fastest rapid cooling rate, the cooling rate is preferably 1,000,000°C / sec or less, and from the viewpoint of actual production, the cooling rate is more preferably 100,000°C / sec or less, and further preferably 10,000°C / sec or less. The atmosphere during rapid cooling is the same as that during dissolution, preferably a low moisture content, inert atmosphere.
[0205] As described above, the crystallinity of the sulfide solid electrolyte including the sulfide glass phase can be adjusted by the cooling rate described above in addition to the method of adding a compound serving as crystal nuclei to the raw material and the method of adding a compound serving as crystal nuclei to the melt.
[0206] The solid obtained in step a3 may be used as a sulfide solid electrolyte as it is, or may be used as a sulfide solid electrolyte after being pulverized and dried according to the application and the like.
[0207] 《Manufacturing method b》
[0208] Process b1-1
[0209] like Figure 3 As shown, step b1-1 in manufacturing method b is a step of mixing raw materials as step S21a. Specifically, except that the raw materials containing halogen elements must be mixed, the raw material mixture is obtained in the same manner as step a1-1 in the above-mentioned manufacturing method a, and the preferred mode is also the same. It should be noted that when halogen is not required as a constituent element of the obtained sulfide solid electrolyte, mixing of raw materials containing halogen elements is not necessary.
[0210] Process b1-2
[0211] like Figure 3 As shown, in step b1-2, as step S21b, the raw material mixture obtained in step b1-1 is sealed in a sealed container.
[0212] The sealed container is not particularly limited as long as it is a heat-resistant container that can be sealed, and examples thereof include heat-resistant containers made of carbon, heat-resistant containers containing oxides such as quartz, quartz glass, borosilicate glass, aluminosilicate glass, aluminum oxide, zirconium oxide, and mullite, heat-resistant containers containing nitrides such as silicon nitride and boron nitride, heat-resistant containers containing carbides such as silicon carbide, etc. In addition, these heat-resistant containers may be a main body formed of the above-mentioned materials, or may be a container formed with a layer of oxide, nitride, carbide, etc.
[0213] When the raw material mixture is sealed in a sealed container, a vacuum atmosphere is preferably used from the viewpoint of not increasing the internal pressure, but a trace amount of an inert gas such as nitrogen or argon may be mixed therein.
[0214] The pressure in the sealed container is not particularly limited as long as it is 1 to 2 atmospheres or less at the melting temperature, but a vacuum is preferred from the viewpoint of not increasing the internal pressure.
[0215] The dew point in the sealed container is preferably -20° C. or lower from the viewpoint of preventing side reactions with water vapor, oxygen, etc. The lower limit is not particularly limited, but is usually about -80° C. The oxygen concentration is preferably 1000 ppm or lower.
[0216] Process b2
[0217] like Figure 3 As shown, step b2 is a step of heating the sealed container in which the raw material mixture is sealed in step b1-2, and heating and melting the raw material mixture as step S22 to obtain a molten product.
[0218] The temperature for heating and melting is preferably 600 to 950° C., more preferably 630 to 900° C., and even more preferably 650 to 850° C. Here, from the viewpoint of improving the fluidity of the melt to allow the reaction of sulfur introduction to proceed or homogenizing the melt, the temperature for heating and melting is preferably 600° C. or higher, more preferably 630° C. or higher, and even more preferably 650° C. or higher. In addition, from the viewpoint of suppressing the degradation and decomposition of the components in the melt due to heating, the temperature for heating and melting is preferably 950° C. or lower, more preferably 900° C. or lower, and even more preferably 850° C. or lower.
[0219] The heating and melting time is preferably 0.1 to 10 hours, more preferably 0.5 to 9.5 hours, further preferably 0.7 to 9 hours, and particularly preferably 1 to 9 hours. Here, from the viewpoint of advancing the reaction of sulfur introduction, the heating and melting time is preferably 0.1 hour or more, more preferably 0.5 hour or more, further preferably 0.7 hour or more, and further preferably 1 hour or more. In addition, from the viewpoint of suppressing the degradation and decomposition of the components in the melt due to heating, the heating and melting time is preferably 10 hours or less, more preferably 9.5 hours or less, and further preferably 9 hours or less.
[0220] When the raw material mixture is directly added to the sealed container and heated and melted, the gas containing elemental sulfur is not introduced from the outside. However, with the heating of the sealed container, a large amount of S from the raw materials or sulfur raw materials volatilizes in the sealed container. Therefore, this step b2 is equivalent to the heating and melting in the gas atmosphere containing elemental sulfur in step 2 of the manufacturing method i.
[0221] Process b3
[0222] like Figure 3 As shown, step b3 is a step of rapidly cooling the melt obtained in step b2 at a cooling rate of 500° C. / sec or more as step S23 to obtain a solid.
[0223] Specifically, except that the front end of the sealed container is broken and the container is subjected to rapid cooling using rapid cooling rollers or the like, the process is the same as step a3 in the above-mentioned production method a, and the preferred aspects are also the same.
[0224] As mentioned above, the sulfide solid electrolyte and the manufacturing method thereof according to the present embodiment have been described in detail. Another aspect of the sulfide solid electrolyte according to the present embodiment is as follows.
[0225] [1] A sulfide solid electrolyte comprising a sulfide glass phase,
[0226] Contains PS4 unit and P2S7 unit,
[0227] The peak intensity I of the above PS4 unit in the Raman spectrum (PS4) The peak intensity of the P2S7 unit I (P2S7) The ratio satisfies 0.05<{I (P2S7) / I (PS4)}<1.00,
[0228] As constituent elements, it contains Li, P, S and Ha.
[0229] The above Ha is a halogen element,
[0230] The contents of the above constituent elements are expressed in at% as Li: 30 to 50%, P: 5 to 15%, and S: 30 to 60%.
[0231] [2] The sulfide solid electrolyte according to [1] above, wherein the Ha comprises at least one selected from the group consisting of F, Cl, Br and I, and the contents of the above constituent elements are expressed in at% as Li: 30 to 50%, P: 5 to 12%, S: 30 to 50% and Ha: 2 to 10%.
[0232] [3] The sulfide solid electrolyte according to [1] or [2], further comprising a P2S6 unit,
[0233] The peak intensity I of the above P2S6 unit in the Raman spectrum (P2S6) The peak intensity I of the P2S7 unit (P2S7) The ratio satisfies 0.5<{I (P2S7) / I (P2S6) The relationship between}<10.
[0234] [4] The sulfide solid electrolyte according to any one of [1] to [3] above, wherein the content ratio of Li to P in the above constituent elements expressed in at % satisfies the relationship of 2.5≤(Li / P)≤7.
[0235] [5] The sulfide solid electrolyte according to any one of [1] to [4], wherein in the Raman spectrum, at a wave number of 150 to 180 cm -1 The region has a peak,
[0236] The full width at half maximum of the above peak is 20 cm -1 above.
[0237] [6] The sulfide solid electrolyte according to any one of [1] to [5] above, wherein the content of the sulfide glass phase is 50% by weight or more.
[0238] [7] The sulfide solid electrolyte according to any one of [1] to [6] above, which is used for a lithium ion secondary battery.
[0239] [8] A method for producing a sulfide solid electrolyte, comprising the following steps:
[0240] Raw materials containing lithium, sulfur and phosphorus are mixed to obtain a raw material mixture,
[0241] The raw material mixture is heated and melted in a gas atmosphere containing sulfur element to obtain a molten material, and
[0242] The molten material is rapidly cooled to obtain a solid.
[0243] The content ratio of the lithium element to the phosphorus element in the raw material mixture expressed in at% is Li / P≥2.5,
[0244] The cooling rate of the rapid cooling is 500° C. / sec or more.
[0245] [9] The method for producing a sulfide solid electrolyte according to [8] above, wherein a raw material containing a halogen element is further mixed to obtain the raw material mixture.
[0246]
[10] The method for producing a sulfide solid electrolyte according to [8] or [9] above, wherein the heating temperature for the heating and melting is 600 to 950°C.
[0247]
[11] The method for producing a sulfide solid electrolyte according to any one of [8] to
[10] above, wherein the contents of the elements when the raw materials are mixed are expressed in at% as Li: 30 to 50%, P: 5 to 15%, and S: 30 to 60%.
[0248]
[12] A method for producing a sulfide solid electrolyte according to any one of [8] to
[11] above, wherein the contents of the elements when mixing the above raw materials are expressed in at% as Li: 30 to 50%, P: 5 to 12%, S: 30 to 50% and Ha: 2 to 10%.
[0249] Example
[0250] The present invention is specifically described below with reference to examples, but the present invention is not limited thereto.
[0251] Examples 1 and 4 to 10 are embodiments, and Examples 2 and 3 are comparative examples.
[0252] [Example 1]
[0253] In a dry nitrogen atmosphere, lithium sulfide powder (manufactured by Sigma, purity 99.98%), phosphorus pentasulfide powder (manufactured by Sigma, purity 99%) and lithium bromide powder (manufactured by Sigma, purity 99.995%) are weighed in a manner to obtain the composition (mol %) described in Table 1, and mixed in the same atmosphere with a mixer (manufactured by WARING, X-TREME (MX1100XTM)) in High mode for 1 minute to obtain a raw material mixture (process b1-1). The obtained raw material mixture is placed in a carbon-coated quartz tube and sealed in a vacuum atmosphere (process b1-2). Directly heat at 750°C for 1 hour to obtain a melt of the raw material mixture (process b2). In a molten state, the front end of the carbon-coated quartz tube is destroyed, and a rapid cooling roller is used to cool at 5000°C / second to obtain a sulfide solid electrolyte (process b3).
[0254] Here, in the step b2, no gas containing sulfur is introduced from the outside. However, since a large amount of S from the raw material is volatilized, the step b2 corresponds to heating and melting in a gas atmosphere containing sulfur.
[0255] In addition, the blank column in "Composition (mol %)" in Table 1 means that nothing other than inevitable impurities contained in the raw materials is actively added.
[0256] The composition of the obtained sulfide solid electrolyte was determined by composition analysis, and it was confirmed that it was roughly consistent with the charge ratio, that is, the value of "Composition (mol%)" in Table 1. It should be noted that roughly consistent means that the difference with the charge composition ratio is within ±5%. Therefore, the "Composition (at%)" in Table 1 is converted from the charge ratio, that is, the "Composition (mol%)" in Table 1, and can be regarded as the content (at%) of the constituent elements of the obtained sulfide solid electrolyte. The same applies to Examples 2 to 10.
[0257] [Example 2]
[0258] In a dry nitrogen atmosphere, lithium sulfide powder (manufactured by Sigma, purity 99.98%) and phosphorus pentasulfide powder (manufactured by Sigma, purity 99%) are weighed in a manner to obtain the composition (mol %) described in Table 1, and mixed in the same atmosphere with a mixer (manufactured by WARING, X-TREME (MX1100XTM)) in High mode for 1 minute to obtain a raw material mixture (process b1-1). The obtained raw material mixture is loaded into a carbon-coated quartz tube and sealed in a vacuum atmosphere (process b1-2). Directly heat at 750°C for 1 hour to obtain a melt of the raw material mixture (process b2). Next, the carbon-coated quartz tube is directly cooled in water at 30°C / second to obtain a sulfide solid electrolyte.
[0259] [Example 3]
[0260] In a dry nitrogen atmosphere, lithium sulfide powder (manufactured by Sigma, purity 99.98%), phosphorus pentasulfide powder (manufactured by Sigma, purity 99%), and lithium bromide powder (manufactured by Sigma, purity 99.995%) were weighed to give the composition (mol%) described in Table 1, and mechanically ground at 400 rpm for 20 hours in a planetary ball mill using ZrO2 balls with a diameter of 4 mm in the same atmosphere to obtain a sulfide solid electrolyte. It should be noted that Example 3 is different from Examples 1 and 2 in that a solid is not obtained by cooling, so the cooling rate in Table 1 is "-".
[0261] [Example 4~Example 10]
[0262] A sulfide solid electrolyte was obtained in the same manner as in Example 1, except that lithium chloride powder (manufactured by Sigma, purity 99.99%), lithium iodide powder (manufactured by Sigma, purity 99.99%), and SiO2 (manufactured by ASONE, crushed quartz test tube SJT series) were appropriately used as raw materials together with lithium bromide powder (manufactured by Sigma, purity 99.995%) or instead of lithium bromide powder (manufactured by Sigma, purity 99.995%) so as to have the composition (mol %) recorded in Table 1.
[0263] [evaluate]
[0264] Crystallinity
[0265] The sulfide solid electrolyte was crushed in a mortar and passed through a 100 μm sieve to obtain a solid electrolyte powder with an average particle size D50 of about 20 μm. Then, an X-ray diffraction apparatus (SmartLab manufactured by Rigaku Corporation) was used with a radiation source of CuKα radiation. The measurement was performed under the conditions of tube voltage: 45 kV, tube current: 200 mA, scanning angle: 10-100°, scanning speed: 5° / min, and step number: 0.01° / step in an environment without exposure to the atmosphere.
[0266] The presence or absence of a crystal peak was confirmed by the obtained XRD pattern, and the types of crystals present are shown in Table 1. In addition, silicon powder was added as an internal standard during XRD measurement, and the crystallinity (weight %) was determined by Rietveld analysis. The crystallinity was subtracted from 100 weight % to calculate the content (weight %) of the sulfide glass phase. The results are shown in Table 1.
[0267] 《PS4 unit, P2S7 unit, P2S6 unit》
[0268] The sulfide solid electrolyte was crushed in a mortar and passed through a 100 μm sieve to obtain a solid electrolyte powder having an average particle size D50 of about 20 μm. The obtained solid electrolyte powder was made into particles with a diameter of 1 cm, and Raman spectrometry was performed on 10 random points in an environment without exposure to the atmosphere (device name: LabRAM HR Evolution manufactured by Horiba, Ltd.).
[0269] The measurement conditions were as follows: excitation wavelength: 532 nm, sample irradiation power: 5 mW, objective lens: 10x, numerical aperture: 0.25, confocal pinhole: 200 μm, grating: 1200 gr / mm, measurement time: 3 sec×10 times, spot diameter: 3 μm.
[0270] For reference, the spectrum obtained in Example 1 is shown in Figure 4 ,like Figure 5As shown in FIG. 1 , the corrected spectrum after baseline correction of the Raman spectrum is obtained. Next, as Figure 6 As shown, the peak separation is performed on the correction spectrum using a mixed function of Gaussian function and Lorentz function. The mixed function refers to the use of Gaussian function and Lorentz function,
[0271] It is expressed by f(x) = (1-M)(Gaussian function) + (M)(Lorentz function),
[0272] The value of M, which represents the mixing ratio of the function (% Lorentz function), is 0.25.
[0273] After peak separation, the peaks will be at wave numbers 415-425 cm -1 The peak with a peak top is the peak of the PS4 unit, which will be at wave number 402-412 cm -1 The peak with a peak top is the peak of the P2S7 unit, which will be at the wave number of 383-393 cm -1 The peak having a peak top is regarded as the peak of the P2S6 unit.
[0274] When the peak separation was performed to separate the three peaks, at 330 cm -1 ~460cm -1 Then, for wave numbers 415 to 425 cm -1 The peak with peak top has the full width at half maximum fixed at 15cm -1 , for wave numbers 402 to 412 cm -1 The peak with peak top has the full width at half maximum fixed at 15cm -1 , for wave numbers 383 to 393 cm -1 The peak with peak top has a fixed full width at half maximum of 22cm -1 The least square method is used for optimization to minimize the difference between the spectrum obtained by subtracting the baseline and the calculated spectrum obtained by adding the peak separated peaks.
[0275] As described above, regarding Example 1, the Raman spectra are shown in Figure 4 The Raman spectrum and the baseline-corrected spectrum are shown in Figure 5 The three spectra obtained by separating the correction spectrum and the peak are shown in Figure 6 It should be noted that Figure 6 A calculated spectrum obtained by adding three peaks obtained by peak separation is also shown, and it is verified that the peak separation is appropriately performed based on the approximation between the correction spectrum and the calculated spectrum.
[0276] In addition, Figure 7 The corrected spectrum of Example 2, the three spectra obtained by peak separation, and the calculated spectrum obtained by adding the three peaks obtained by peak separation are shown in FIG. Figure 82 shows the corrected spectrum of Example 3, three spectra obtained by peak separation, and a calculated spectrum obtained by adding the three peaks obtained by peak separation.
[0277] As described above, the highest intensity of each peak obtained by peak separation, that is, the intensity of the peak top, is defined as the peak intensity, and the peak intensity of the PS4 unit is defined as I (PS4) , set the peak intensity of the P2S7 unit to I (P2S7) , the peak intensity of the P2S6 unit is set to I (P2S6) , find {I (P2S7) / I (PS4} and {I (P2S7) / I (P2S6) The results are shown in Table 1.
[0278] In addition, in the Raman spectrum, it was confirmed that the -1 The peak was found in the region of , and when the peak was observed, the full width at half maximum was calculated. The results are shown in Table 1
[0279] 《Lithium Ion Conductivity》
[0280] The sulfide solid electrolyte was crushed in a mortar and passed through a 100 μm sieve to obtain a solid electrolyte powder with an average particle size D50 of about 20 μm. The obtained solid electrolyte powder was made into a powder compact under a pressure of 380 kN as a measurement sample. The AC impedance measurement of the measurement sample was performed using an AC impedance measurement device (manufactured by Bio-Logic Sciences Instruments, potentiostat / galvanostat VSP) with a measurement frequency of 100 Hz to 1 MHz, a measurement voltage of 100 mV, and a measurement temperature of 25°C. The lithium ion conductivity was calculated based on the obtained Nyquist curve. The results are shown in "σ 25 ”.
[0281]
[0282] According to the above results, the sulfide solid electrolyte involved in the present embodiment contains a sulfide glass phase and can achieve high lithium ion conductivity. This is achieved because the uniformity of the glass obtained through the molten state is high, and in addition, it mainly contains PS4 units relative to the P2S7 units. For the sulfide solid electrolyte involved in Example 2, the lithium ion conductivity is low regardless of whether the sulfide glass phase exceeds 90% by weight. It is believed that this is because the proportion of P2S7 units in Example 2 is high compared to the sulfide solid electrolytes involved in Examples 1 and Examples 4 to 10.
[0283] In addition, as a reference example, a sulfide solid electrolyte was produced in the same manner as in Example 2 so as to have the composition of Example 1. As a result, it was confirmed that a crystal peak was observed by XRD measurement, and it was also confirmed that the lithium ion conductivity was less than 0.06 mS / cm, and the desired sulfide solid electrolyte containing a sulfide glass phase was not obtained.
[0284] Although the present invention has been described in detail with reference to specific embodiments, it is apparent to those skilled in the art that various changes and modifications may be made without departing from the spirit and scope of the present invention. This application is based on Japanese patent application (Japanese Patent Application No. 2022-114970) filed on July 19, 2022, the contents of which are incorporated herein by reference.
Claims
1. A sulfide solid electrolyte comprising a sulfide glass phase, Contains PS4 unit and P2S7 unit, The peak intensity of the PS4 unit in the Raman spectrum is (PS4) The peak intensity of the P2S7 unit I (P2S7) The ratio satisfies 0.05<{I (P2S7) / I (PS4) }<1.00, As constituent elements, it contains Li, P, S and Ha. Said Ha is a halogen element, The contents of the constituent elements are expressed in at% as Li: 30 to 50%, P: 5 to 15%, and S: 30 to 60%.
2. The sulfide solid electrolyte according to claim 1, wherein As the Ha, at least one selected from the group consisting of F, Cl, Br and I is included, The contents of the constituent elements are expressed in at% as Li: 30 to 50%, P: 5 to 12%, S: 30 to 50%, and Ha: 2 to 10%.
3. The sulfide solid electrolyte according to claim 1 or 2, wherein further comprising a P2S6 unit, The peak intensity I of the P2S6 unit in the Raman spectrum (P2S6) The peak intensity of the P2S7 unit I (P2S7) The ratio satisfies 0.5<{I (P2S7) / I (P2S6) The relationship between}<10.
4. The sulfide solid electrolyte according to claim 1 or 2, wherein Among the constituent elements, the content ratio of Li to P expressed in at% satisfies the relationship of 2.5≤(Li / P)≤7.
5. The sulfide solid electrolyte according to claim 1 or 2, wherein In Raman spectroscopy, at wave numbers between 150 and 180 cm -1 The region has a peak, The full width at half maximum of the peak is 20 cm -1 above.
6. The sulfide solid electrolyte according to claim 1 or 2, wherein The content of the sulfide glass phase is 50% by weight or more. 7 . The sulfide solid electrolyte according to claim 1 , which is used in a lithium ion secondary battery.
8. A method for producing a sulfide solid electrolyte, comprising the following steps: Raw materials containing lithium, sulfur and phosphorus are mixed to obtain a raw material mixture, The raw material mixture is heated and melted in a gas atmosphere containing sulfur element to obtain a molten material, and The melt is rapidly cooled to obtain a solid. The content ratio of the lithium element to the phosphorus element in the raw material mixture expressed in at% is Li / P≥2.5, The cooling rate of the rapid cooling is 500° C. / sec or more.
9. The method for producing a sulfide solid electrolyte according to claim 8, wherein: The raw materials containing halogen elements are further mixed to obtain the raw material mixture.
10. The method for producing a sulfide solid electrolyte according to claim 8 or 9, wherein: The heating temperature of the heating and melting is 600-950°C.
11. The method for producing a sulfide solid electrolyte according to claim 8 or 9, wherein: The contents of the elements when the raw materials are mixed are expressed in at% as Li: 30 to 50%, P: 5 to 15%, and S: 30 to 60%.
12. The method for producing a sulfide solid electrolyte according to claim 8 or 9, wherein: The contents of the elements when the raw materials are mixed are expressed in at% as Li: 30 to 50%, P: 5 to 12%, S: 30 to 50%, and Ha: 2 to 10%.
Citation Information
Patent Citations
Solid electrolyte
JP2014093262A
Toy component and toy doll
JP2022114970A
Lithium ion conductive sulfide-based solid electrolyte and all-solid lithium battery using same
WO2007066539A1